2002
DOI: 10.1038/sj.cgt.7700463
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus–mediated gene transfer of endostatin inhibits angiogenesis and tumor growth in vivo

Abstract: A variety of approaches has demonstrated that interfering with tumor -induced angiogenesis may be an effective strategy in cancer therapy. However, it is likely that to be most effective such strategies will require extended suppression of the angiogenic process. Gene therapy offers a possible approach to achieve sustained release of a therapeutically potent transferred gene product. In the present study the angiogenesis inhibitor endostatin was expressed through a recombinant adeno -associated viral ( rAAV ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 40 publications
0
29
1
Order By: Relevance
“…Furthermore, the inhibition of tumor growth was possible using AAV-based vectors expressing appropriate levels of endostatin. [30][31][32][33][34] Initially, we set out to treat spontaneous tumors in canines using AAV-mediated canine FcEndostatin (cFcES). Canines develop spontaneous tumors and serve as a suitable model for human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the inhibition of tumor growth was possible using AAV-based vectors expressing appropriate levels of endostatin. [30][31][32][33][34] Initially, we set out to treat spontaneous tumors in canines using AAV-mediated canine FcEndostatin (cFcES). Canines develop spontaneous tumors and serve as a suitable model for human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 However, serum endostatin levels of 35-40 ng/ml have been shown to be sufficient for exerting an antiangiogenic effect in vivo, suggesting that our delivery system induced therapeutically relevant plasma endostatin levels. 37 Taken together, our mRNA and protein detection experiments showed that intra-tumoral administration with Ad/hEndo should most likely be repeated at intervals of 2 or 3 weeks to maintain sufficient intra-tumoral endostatin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…128 Shi et al demonstrated that intramuscular injection of rAAV2/human endostatin vectors led to sustained serum transgene expression which significantly inhibited tumor vessel formation and tumor growth. 130 Tumor growth was also significantly reduced following transduction with AAV2/Timps vectors (tissue inhibitors of matrix metalloproteinases) into Kaposi'sarcoma engrafted nude mice. 133 Since various antiangiogenesis proteins prevent tumor vascularization through different mechanisms, it has been suggested that a combination of therapies utilizing different antiangiogenesis agents potentiates an additive inhibitory effect on tumor growth.…”
Section: Antiangiogenesis Therapymentioning
confidence: 97%
“…126 To date, AAV2-based vectors have been used to deliver different antiangiogenesis genes to tumors in animal models with promising results. [127][128][129][130][131] Ma et al used an AAV2/angiostatin vector to treat human glioma in an animal model. Following either intratumoral or intramuscular injection with this vector, approximately 40% of the animals survived for over 10 months free of tumors.…”
Section: Antiangiogenesis Therapymentioning
confidence: 99%